2010
DOI: 10.1037/a0017703
|View full text |Cite
|
Sign up to set email alerts
|

Are birds smarter than mathematicians? Pigeons (Columba livia) perform optimally on a version of the Monty Hall Dilemma.

Abstract: The “Monty Hall Dilemma” (MHD) is a well known probability puzzle in which a player tries to guess which of three doors conceals a desirable prize. After an initial choice is made, one of the remaining doors is opened, revealing no prize. The player is then given the option of staying with their initial guess or switching to the other unopened door. Most people opt to stay with their initial guess, despite the fact that switching doubles the probability of winning. A series of experiments investigated whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
104
4
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(127 citation statements)
references
References 32 publications
18
104
4
1
Order By: Relevance
“…To examine the performance of humans on a task conceptually similar to that in Zentall and Stagner, an analog task in the form of a video game was developed. Exploration of similarities and differences between human and nonhuman learning processes can be simplified by the use of video games with humans (e.g., Herbranson, Fremouw, & Shrimp, 1999Herbranson & Shroeder, 2010;Madden, Ewan, & Lagorio, 2007;Rayburn-Reeves, Molet, & Zentall, 2011;Rosati & Stevens, 2009). In our computer task, participants chose between two alternatives (two planetary systems: ZORB or ARTO).…”
Section: Methodsmentioning
confidence: 99%
“…To examine the performance of humans on a task conceptually similar to that in Zentall and Stagner, an analog task in the form of a video game was developed. Exploration of similarities and differences between human and nonhuman learning processes can be simplified by the use of video games with humans (e.g., Herbranson, Fremouw, & Shrimp, 1999Herbranson & Shroeder, 2010;Madden, Ewan, & Lagorio, 2007;Rayburn-Reeves, Molet, & Zentall, 2011;Rosati & Stevens, 2009). In our computer task, participants chose between two alternatives (two planetary systems: ZORB or ARTO).…”
Section: Methodsmentioning
confidence: 99%
“…For example, pigeons distributed a higher proportion of their responses to the higher-paying alternative than did humans in procedurally equivalent tasks (Goodie & Fantino, 1995Hartl & Fantino, 1996). Some research teams have reported that nonhuman animals appear to respond in a way that better maximizes payoffs than humans to probabilistic game-like tasks such as the Monty Hall Dilemma (e.g., Herbranson & Schroeder, 2010), although this is not always the case (e.g., Klein, Evans, Schultz, & Beran, 2013;Mazur & Kahlbaugh, 2012).…”
Section: Discussionmentioning
confidence: 93%
“…It turns out that if you want advice on how to best play the game, ask a pigeon. Herbranson and Schroeder (2010) gave pigeons and humans repeated chances to play the Monty Hall game and found, again, that humans failed to adopt optimal strategies, even with extensive training. But pigeons Figure 4.…”
Section: The Monty Hall Problem and Misrepresenting Probabilitymentioning
confidence: 99%